Genome-wide association study (GWAS)-identified disease risk alleles do not compromise human longevity - Beekman, Marian (National Academy of Sciences, 2010)
A set of currently known alleles increasing the risk for coronary artery disease, cancer, and type 2 diabetes as identified by genome-wide association studies was tested for compatibility with human longevity. Here, we show that nonagenarian siblings from long-lived families and singletons older than 85 y of age from the general population carry the same number of disease risk alleles as young controls. Longevity in this study population is not compromised by the cumulative effect of this set of risk alleles for common disease.